Cystatin C, E-glomerular Filtration Rate and Creatinine are Considered as a Marker in Iraqi Patients with Chronic Kidney Disease - Mohammed Qasim Waheeb (Journal of Global Pharma Technology, 2018)
People with diminished glomerular filtration rate (GFR) are at more serious hazard for cardiovascular disease and different comorbidities. Creatinine-based conditions are utilized to estimate GFR, recognize patients with potential kidney disease, and arrange them into various stages since serum creatinine is uncaring to changes in the GFR.The aim of study to assess analytic execution of serum cystatin C e-glomerular filtration rate and creatinine as markers of kidney function in patients. Sixty cases at various stages of renal disability and 30 healthy control groups were tried. serum cystatin C were higher in stage 2 chronic kidney disease (CKD) when contrasted with the control gathering (p<0.05). For stages 3– 5 the median levels of cystatin C and creatinine were observed to be essentially higher than the control group.Keywords CKD, EGFR, Cystatin, Creatinine.